Inadequate control of heart rate in patients with stable angina: results from the European Heart Survey. Issue 1014 (30th March 2010) - Daly, Caroline A; Clemens, Felicity; Lopez Sendon, Jose L; Tavazzi, Luigi; Boersma, Eric; Danchin, Nicolas; Delahaye, François; Gitt, Anselm; Julian, Desmond; Mulcahy, David; Ruzyllo, Witold; Thygesen, Kristian; et al.
Abstract : Aims: To examine resting heart rate (HR) in a population presenting with stable angina in relation to prior and subsequent pharmacological treatment, comorbid conditions and clinical outcome. Methods and results: The European Heart Survey was a prospective, observational, cohort study of 3779 patients with stable angina newly presenting to cardiology services. Mean baseline resting HR was 73 beats/min (bpm) and 52.3% of patients had a baseline HR > 70 bpm. Over half of patients were on no chronotropic medication at baseline. Patients with chronic respiratory disease or diabetes had higher resting HRs (75–76 bpm), and were more likely to have been receiving calcium channel blockers at baseline assessment. Overall, β-blockers were the most common treatment administered following cardiologist assessment, but were used less frequently in patients with chronic respiratory disease and diabetes, and the dosages used were less than that found to be effective in clinical trials. Mean daily doses of metoprolol, bisoprolol, carvedilol, and atenolol were 75 mg, 6 mg, 19 mg and 55 mg, respectively. Higher HR at baseline was associated with higher rates of cardiovascular mortality and hospitalisation for heart failure. Conclusion: Control of ischaemic symptoms through heart rate modification in patients with angina is currently inadequate, both by primary referring physicians and cardiologists. Given the adverse outcome associated with higher resting heart rates in this as in other studies, and the availability of specific HR reducing strategies, attention should be given to achieving optimal HR control.